A Brief Review of Ground Penetrating Radar Investigation Results of Ice Caps on Galindez, Winter and Skua Islands (Wilhelm Archipelago, Antarctica) for the Period April 2017 – January 2019 - A. Chernov; K. Lamsters; J. Karušs; M. Krievāns; Yu. Otruba (Ukrainian Antarctic Journal, 2018)
This paper represents results of GPR surveying of the ice caps on Galindez (–64.24716W; –65.24992S), Winter (–64.25954W; –65.24944S) and Skua (–64.26530W; –65.25309S) islands (Wilhelm Archipelago, Antarctica) for the period April 2017 — January 2019.The main objectives were identification of the ice layering, monitoring of interglacial heterogeneities (crevasses, interglacial channels and voids) and measurements of the ice thickness.Methods: Surveying on the glaciers has been done with ground coupled shielded bowtie antenna VIY3-300 (300 MHz) GPR and with air coupled dipole Zond 12-e (75 MHz) antenna system. Monitoring investigation of glacier’s interior has been done with VIY3-300. Zond 12-e was applied mostly for indication of the ice-rock border. Monitoring investigation has been done on one (1) ice cap on Galindez Island, on two (2) ice caps on Winter Island and on two (2) ice caps on Skua Island. Monitoring with VIY3-300 GPR of the ice cap on Galindez Island has been done once per month since April 2017. Four surveys were done on Winter Island: May 2017, January, May and October 2018. Four periods were surveyed on Skua Island: May and September 2017, January—February and October 2018. Monitoring with VIY3-300 has been done on the same position (according to the GPS data) each time. For precise investigation during February—March 2018, islands were covered with a grid of profiles with 25 meters spacing between them.Results: Three (3) to eight (8) strong internal linear reflections are detected in the ice caps, heterogeneities are visible closer to edges of the glaciers, seasonal anomalies in glacier`s interior are observed and a maximum ice thickness of 35 meters on Galindez Island is obtained. Seasonal anomalies were traced better in November—January 2017—2018 than during November—January 2018—2019. Reflection from the ice-rock border is better visible on the data from Zond 12-e, but layering and interior structure are better identified with VIY3-300. This spatial resolution difference evidently happened because central frequency of antenna was 4 times higher in VIY3-300 than in Zond 12-e. Further monitoring of the ice caps on Galindez, Winter and Skua islands is recommended to trace their evolution. It is crucial to continue these scientific observations in the future because changes of small ice caps in West Antarctica are indicators of global warming.